(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
Translation is more than a mere transfer of words from one language to another; it is a delicate process of conveying meaning, context, and cultural nuances. At its core lies semantics, the branch of linguistics concerned with meaning. Understanding the semantic features of translation is crucial for producing translations that are accurate, culturally relevant, and contextually appropriate